Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.21873/anticanres.13013
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein-based Prognostic Measures Are Superior at Predicting Survival Compared with Peripheral Blood Cell Count-based Ones in Patients After Curative Resection for Pancreatic Cancer

Abstract: Aim: Prognostic factors of recurrence and survival in various cancer types have been reported and include Creactive protein (CRP)-based measures as evidenced by the Glasgow prognostic score (GPS), as well as peripheral blood cell-based prognostic values such as the prognostic index (PI), neutrophil-to-lymphocyte ratio (NLR), and platelet-tolymphocyte ratio (PLR). The aim of this study was to identify significant prognostic values and compare them for suitability for use in patients after curative pancreatic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…C-reactive protein) [1,19]. A meta-analysis of 34 studies including 7105 patients with pancreatic cancer revealed that high PLR and NLR were defined as values from 150 to 200, and 2 to 5, respectively [20].…”
Section: Funding: Nonementioning
confidence: 99%
“…C-reactive protein) [1,19]. A meta-analysis of 34 studies including 7105 patients with pancreatic cancer revealed that high PLR and NLR were defined as values from 150 to 200, and 2 to 5, respectively [20].…”
Section: Funding: Nonementioning
confidence: 99%
“…Ultimately, 20 studies [8,[15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] including 6512 patients were enrolled in this meta-analysis after excluding ineligible studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…1, the literature search process was summarized in the ow diagram according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) [23]. Ultimately, 20 studies [8,[15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] including 6512 patients were enrolled in this meta-analysis after excluding ineligible studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%